Beyond The Tacit-Explicit Dichotomy: Towards A Conceptual Framework For Mapping Knowledge Creation, Sharing & Networking - Mughal, Farooq (Journal of Knowledge Management Practice, 2010)
The purpose of this paper is to critically analyze the knowledge sharing mechanisms at the individual-institutional levels which foster transfer of knowledge, resulting into the formation of knowledge networks. In particular, the paper develops an argument based on seven propositions to establish a roadmap for knowledge creation, sharing mechanisms and knowledge networks based on literature review. The basic premise of the argument revolves around the concepts of theorists (e.g. Cook & Brown, 1999; Cabrera & Cabrera, 2002; Boh, 2007) which provide four classifications of knowledge sharing mechanisms. In a theoretical discourse, the analysis suggests that knowledge sharing mechanisms under each classification gives rise to a certain type of knowledge network (based on the nature of knowledge created and mechanism used) during the transfer of knowledge. The author attempts to propose a conceptual framework to map the transfer of knowledge from creation to sharing and networking.The paper is divided into three broad sections. The first section discusses the practices of knowledge management and provides a quick overview of the knowledge creation process. The second section explains the knowledge sharing mechanisms and provides an insight on the formation of knowledge networks. The last section, proposes a conceptual framework to map knowledge creation, sharing and networking based on the theoretical perspectives of researchers.
Keywords: Knowledge management; Knowledge transfer; Knowledge networks; Tacit; Explicit; Knowledge sharing mechanisms; Knowledge creation